Áreas de transição dos condomínios verticais de uso misto e espaços públicos ou privados? - Santos, Luciana Gavazza dos (2017)
The mixed use building has great importance for contemporary urbanism, it is a key element in the compact city, which has among its principles multifunctionality. The mixed use building has the function of revitalizing urban spaces and improving urban mobility, thereby promoting a better quality of life for residents of large and medium-sized cities. The hypothesis is that these private, publicly accessible spaces have both physical and functional characteristics that make them much more private and inaccessible to particular groups of visitors who do not adhere to their invisible codes of behavior. The general objective of this master's thesis in architecture and urbanism is to investigate the perception and the way of appropriation of different users, as to the public / private character of the transition areas of mixed-use buildings in Maceió. For this purpose, a survey was carried out of the 10 mixed-use buildings constructed in Maceió, prior to 2004, and a technical assessment regarding accesses, situation with regard to the sidewalk, whether elevated or at the same level, and the percentage of the private access área public, here called the transition area. In this appreciation the typologies of corner and middle of block (Street to street) stood out as bringing more communication of the building as the street. Another characteristic identified as positive was when the ground floor presented more than one access, creating a circulation inside it, since it can be used not only for consumption in stores, but also as a passage. In addition to the survey of the 10 buildings, a study was also made of two most commonly used mixed-use buildings in Maceió. Jatiúca Trade Residence (JTR) and Maceió Facilities (MF), in which aspects related to security, public vs. private relation, architectural design, and the perception of different users regarding these transitional spaces were investigated. The typology of the ground floor of the MF, gallery type, with greater contact with the street, gives a greater sense of security to the users, different from the JTR (the residents have a feeling of insecurity) where the boulevard, although extensive, has its accesses restricted. As for the public x private characteristic of these spaces, it was perceived that the perception about it among users still needs to be more mature, so that the place becomes in fact accessible to all. As for the architectural project, the ground floor on the same level of the sidewalk, corner lands, more of an access and greater area of transition, were the most accurate design decisions in the researcher's view. The recent mixed-use buildings in Maceió do not have the full features to become in fact sustainable buildings and included in the current compact city concept.